Mechanical exfoliation of graphite to graphene in polyvinylpyrrolidone aqueous solution - L. A. Myroniuk; D. V. Myroniuk; E. V. Maistruk; S. I. Kuryshchuk; A. I. Ievtushenko; I. M. Danylenko; V. V. Strelchuk; I. P. Koziarskyi (Хімія, фізика та технологія поверхні)
In presented work we have reported that polyvinylpyrrolidone (PVP) is suitable organic solvent for mechanical exfoliation of crystalline graphite to graphene in aqueous solution through kitchen blender technique. Morphological, structural and optical, properties of graphene samples were characterized by scanning electron microscopy, Raman scattering and UV-Visible spectroscopy. Scanning electron microscopy demonstrates folded morphology of graphene flakes with ~4 nm thickness. Raman scattering was revealed the high-quality graphene with low levels of defects after the exfoliation process of graphite/PVP dispersions. The G band at ~1582 cm?1 on Raman spectra is related with stretching vibrations of carbon atoms. The broadening of the G band is not observed, that indicated on absence of the basal plane defects in the graphene structure, which can be introduced during exfoliation by the kitchen blender. The ratio of the intensity of 2D and G bands equal to 1.66 (I2D/IG>1) and the value of 2D band full width at half maximum is 79.88 cm–1, indicated a few-layer graphene (FLG) structure. The defects quantity identified by the intensity ratio of the D and G bands, ID/IG is 0.18, significantly lower than that reported for graphene oxide with basal plane defects (> 1) and for sonication dispersed graphene (~ 0.6). The graphene dispersions were characterized by UV–Vis spectroscopy, minimum transmittance observed at around 270 nm is attributed to the ???* transitions of aromatic C–C bonds in graphene. The optical transmittance minimum and the overall high transmittance decreasing values observed between 270 and 800 nm strongly suggest the presence of two-dimensional material in the dispersion, thus confirming the successful exfoliation of graphite to graphene by blending.